2006
DOI: 10.1177/112067210601600125
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Hyperferritinemia Cataract Syndrome: Ocular, Genetic, and Biochemical Findings

Abstract: The morphology of cataracts in HHCS seems to be similar in all cases. In the heterozygous G32C mutation, the age at onset of cataracts is very early. Greater awareness of this condition among ophthalmologists will lead to effective family counseling of those affected, by genetic testing or simple biochemical tests. Serum ferritin levels can be effectively used to screen for this condition in suspected families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
0
14
0
1
Order By: Relevance
“…Some investigators have suggested that opacities of very early onset or of higher density may be due to a more severe genetic mutation of the L-ferritin subunits. 13 In conclusion, HHCS is a recently described cause of inherited cataracts. In patients with characteristic bilateral lenticular opacities and a positive family history, laboratory studies can confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Some investigators have suggested that opacities of very early onset or of higher density may be due to a more severe genetic mutation of the L-ferritin subunits. 13 In conclusion, HHCS is a recently described cause of inherited cataracts. In patients with characteristic bilateral lenticular opacities and a positive family history, laboratory studies can confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…The six-nucleotide loop is connected to a stem that is separated into an upper and lower part by an unpaired bulge C residue that divides the stem in the middle. IRE sequences are highly conserved, and mutations of the IRE can cause iron dysregulation and diseases, suggesting a significant role of IRP/IRE regulation in iron homeostasis (Kato et al, 2001; Ismail et al, 2006). IREs are recognized and bound by IRP proteins, but the effect of IRP binding depends on the position of the IRE in the mRNA targets.…”
Section: Regulation Of Intracellular Iron Homeostasis By the Irp/ire mentioning
confidence: 99%
“…Las opacidades del cristalino en los pacientes con SHHC presentan un aspecto característico y muy similar en todos ellos 7 . Aunque la forma en que han sido descritas es variable [8][9][10] , todas pueden representar diferentes maneras de definir alteraciones parecidas.…”
Section: Discussionunclassified